THE INFLUENCE OF FREE-BODY DIAGRAM REPRESENTATION SKILL TOWARDS THE CONCEPT COMPREHENSION - Galuh Utami; Eko Suyanto; Abdurrahman - (Jurnal Pembelajaran Fisika, 2013)
The material of particle dynamics, notably Newton second law, highly demands students’ ability to analyze and describe the directions of the certain force at one particular system as a mean to assist them in comprehending a concept. The teachers, who involve in the process of teaching the materials, need to choose a visual representation that is supported by other representation formats. Through this technique, students are demnded to comprehend the concept and solve the problems easier. The purpose of this research was to investigate the influence of free-body diagram representation skill towards the comprehension of the concept in particle dynamics material. In line with the purpose, the researcher decided One-Shot Case Study as the research design. Then, Sample class was selected by purposive sampling.The results of this research showed that there was a linear and significant influence of the free body diagram representation skill towards students’ concept comprehension. It was about 43,6%. The degree of relation between free-body diagram representation skill and concept comprehension had a strong relationship and its influence contributed positively.Keywords: Free Body Diagram Representation Skill, Inquiry Learning Model Multiple Representation Based, Concept Comprehension.